SCIENTIFIC INTERPRETATION AND INNOVATION ECONOMY METHODOLOGY - Lidia I. Kochurova (Plekhanov Russian University of Economics, 2017)
The main idea of the article is that there is no alternative for the innovation way of Russia’s development. However, this statement is questionable. The problem is there is no scientifically grounded innovation mechanism either in Russia or abroad. The article provides a scientific definition of the term ‘innovation’, shows signs which can characterize innovation economy and puts forward its methodology. The authors prove that the fundamental basis of innovation economy at the enterprise can be only amortization. On this basis the fund of innovation costs can be formed in the profit, which could release this part of the profit from taxation. Western countries proposed EBITDA index but it has not been scientifically substantiated.